Inclusive Public Service Space For Elderly With Disabilities Balance In Poncol Station District Semarang - Desectasari, Dhiaz Putri; Ristianti, Novia Sari (Universitas Negeri Semarang, 2019)
The public spaces in essence should be able to accommodate the users. Especially with users who have special needs or called user inclusive. One thing that is often overlooked in the application of the space design is elderly. Though the government launched the Elderly Friendly Cities program and one of them is the most populous Semarang in Central Java, 34 percent of the total population. Poncol Station Semarang is an example of public service that is not fully provide even distribution in terms of design. In fact, Poncol station offers ticket price reduction if the purchase is done directly at the station counter by twenty percent of the original price of special elderly where their activities should be contained fully included in the design space that is enterance Pre-Area, parking and drop-off, and the building area is the lounge, counters, toilets and platforms. Therefore, the question arises of research